2004
DOI: 10.1081/jas-200026410
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Childhood Asthma on Parental Quality of Life

Abstract: Measuring the quality of life of caregivers is important for interventions designed for young children with asthma. However, little is known about the impact of childhood asthma on parental quality of life for certain subgroups. This study included the families of young urban children with mild persistent to severe persistent asthma. The goal was to evaluate the relationship between caregivers' quality of life and the children's asthma severity, and to consider the influence of sociodemographic factors on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 31 publications
7
70
0
2
Order By: Relevance
“…Once the caregivers have a higher level of education, they will tend to have more knowledge about asthma and its evolution, what to do when symptoms appear, and how to prevent crises, minimizing the damage to the quality of life of the child. The low level of caregiver education was highly correlated with the socio-economic background of the family, where they have more risk of environmental exposures, access to healthcare facilities, stress, and cultural factors [12]. Our finding also indicated there was no effect of parental education level on exacerbation of asthma frequency.…”
Section: Association Of Socio-demography Characteristics Of Responsupporting
confidence: 65%
“…Once the caregivers have a higher level of education, they will tend to have more knowledge about asthma and its evolution, what to do when symptoms appear, and how to prevent crises, minimizing the damage to the quality of life of the child. The low level of caregiver education was highly correlated with the socio-economic background of the family, where they have more risk of environmental exposures, access to healthcare facilities, stress, and cultural factors [12]. Our finding also indicated there was no effect of parental education level on exacerbation of asthma frequency.…”
Section: Association Of Socio-demography Characteristics Of Responsupporting
confidence: 65%
“…For parents of children with asthma a decreased quality of life is related to missed workdays, limited activities, inadequate sleep, frequent night awakenings and decreased emotional health. In addition, several studies have also indicated a negative relationship between symptom frequency and parental quality of life scores (Halterman et al, 2004;Osman, Baxter-Jones & Helms, 2001) The purpose of this article is to examine the relationship between child and parental quality of life and to describe the relationship among several factors such as demographic variables, asthma severity, missed days of work, asthma education and quality of life in rural children with asthma and their parents/caregivers. Data on quality of life were collected as part of a larger study funded by the National Institute of Nursing Research (NINR), NIH (NR05062) to evaluate the effectiveness of a school based asthma education intervention for rural elementary school age children with asthma (Butz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many self-management asthma interventions have demonstrated an increase in asthma knowledge (7)(8)(9), reduced emergency department visits (10), increased self-efficacy (11)(12), and quality of life (13)(14). The type of self-management interventions, specifically individualized and interactive educational interventions, have been suggested to have the strongest effect on asthma morbidity (10).…”
Section: Introductionmentioning
confidence: 99%